Relational Spirituality and Transgenerational Obligations: The Role of Family in Lay Explanatory Models of Post-traumatic Stress Disorder in Male Cameroonian Asylum Seekers and Undocumented Migrants in Europe - Grupp, Freyja; Skandrani, Sara; Moro, Marie Rose; Mewes, Ricarda (Frontiers in Psychiatry, 2021)
Context: Diasporic Cameroonians are increasingly leading a transnational life in which family members are sustained through networks of relations and obligations. However, before arriving in Europe, the vast majority of African migrants who take the Mediterranean route are exposed to trauma and hardship. Moreover, the joint occurrence of forced displacement, trauma, and extended separation from families has a significant impact on mental health. Objectives: This study explores the role of culture-specific conceptualizations of family structures and transnationalism in explanatory models of posttraumatic stress disorder (PTSD) among male Cameroonian asylum-seekers and undocumented migrants in Europe. Methods: An in-depth study of two samples of Cameroonian migrants with a precarious residency status in Europe was conducted. Focus group discussions and interviews were carried out with asylum seekers in Germany (n=8) and undocumented migrants and failed asylum seekers in France (n=9). The verbatim transcripts of these interviews served as the data for interpretative phenomenological analyses. Results, Analysis, and Discussion: Family was conceptualized in religious and spiritual terms, and relational spirituality appeared to be a crucial element of family cohesion. Explanatory models of PTSD were mainly based on an intersection of family and spirituality. The disrespect of transgenerational, traditional, and spiritual obligations towards parents and ancestral spirits represented a crucial causal attribution for posttraumatic symptoms. Conclusions: Conceptualizations of posttraumatic stress were based on a collective family and spiritual level instead of an individualized illness-centered perception. The Western psychological and psychiatric perspective on posttraumatic stress might conflict with traditional, religious, and spiritual practices in the context of family conceptualizations of Cameroonian forced migrants with a precarious residency status.